(untitled) (Journal of Parents and Teachers, 2014)
This article talks about the pleasure of reading. It claims reading to be a priority activity in kid’s lives (pupils or one’s own kids). It is necessary to reflect about reading, visit libraries, know their resources and discover its charms to make activities like: individual reading, silent or aloud, drawing posters, perform poems and tales, exhibitions and authors’ meetings.